2007
DOI: 10.1080/10409230701648502
|View full text |Cite
|
Sign up to set email alerts
|

Mutation as a Stress Response and the Regulation of Evolvability

Abstract: Our concept of a stable genome is evolving to one in which genomes are plastic and responsive to environmental changes. Growing evidence shows that a variety of environmental stresses induce genomic instability in bacteria, yeast, and human cancer cells, generating occasional fitter mutants and potentially accelerating adaptive evolution. The emerging molecular mechanisms of stressinduced mutagenesis vary but share telling common components that underscore two common themes. The first is the regulation of muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
458
1
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 567 publications
(474 citation statements)
references
References 200 publications
(312 reference statements)
9
458
1
6
Order By: Relevance
“…Other mechanisms that can also increase genetic variation when condition is poor or during stress include mutagenesis [15,88], loss of heterozygosity [89], genomic rearrangements [90], aneuploidy [91,92], dispersal [14,16], mate choice [93] and even death-resulting in the replacement of an aging individual by a young one, generated through sex and mutation [94].…”
Section: Generalization: Condition-dependent Variationmentioning
confidence: 99%
“…Other mechanisms that can also increase genetic variation when condition is poor or during stress include mutagenesis [15,88], loss of heterozygosity [89], genomic rearrangements [90], aneuploidy [91,92], dispersal [14,16], mate choice [93] and even death-resulting in the replacement of an aging individual by a young one, generated through sex and mutation [94].…”
Section: Generalization: Condition-dependent Variationmentioning
confidence: 99%
“…Together with other colleagues, Genevieve and I were able to identify several regulatory factors involved in the starvation response (RpoS, ClpXP, Lon, HN-S, and Crp) ( Figure 5; Gomez-Gomez et al 1997;Lamrani et al 1999). As has subsequently been discovered for other adaptive mutation systems in bacteria, aerobic starvation leads to signal transduction events and an increase in the genome restructuring activities of transposable elements as well as the SOS system and plasmid transfer functions (Peters and Benson 1995;Taddei et al 1995;Hall 1999;Bjedov et al 2003;Horak et al 2004;Foster 2007;Galhardo et al 2007).…”
Section: Regulating Transposable Element Activity: Mu Activation Adamentioning
confidence: 99%
“…6,7 Importantly, stress-induced mutagenesis has many parallels to the adaptation of cancer cells to growth-limiting conditions and stress and therefore may have implications for cancer progression and the ability of tumor cells to develop resistance to therapy. 3 The central mechanism of adaptive mutagenesis in E. coli has been revealed by several years of elegant genetic studies which have identified Y-family translesion DNA polymerase IV (pol IV), also known as DinB, as the major driver of stressinduced mutations. 1,2,8 Pol IV is highly upregulated to ~2500 molecules/cell during the SOS response and is further induced by an additional ~2-fold to ~5000 molecules/cell during stationary phase by the RpoS general stress response.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] For example, adaptive mutagenesis has been shown to promote antibiotic resistance, which is becoming a major threat to modern medicine. 4,5 It is now evident that stress-induced mutations occur on both episomal and chromosomal DNA and promote the survival of laboratory strains and natural isolates of bacteria under conditions of stress.…”
Section: Introductionmentioning
confidence: 99%